Monitoring cathodic protection system for underground pipeline - Thai, Seng Choong (2013)
The world we live in today is greatly affected by corrosion issues and therefore multiple methods of continuous monitoring of a structure can help investigate the corrosion process. Till today, engineers have found that Cathodic Protection is one of the most reliable solutions to overcome corrosion problems. The principle of cathodic protection is a process of placing an external anode to the metal of the pipe in order for its metal surface to become cathodic and thus preventing corrosion. The most common cathodic protection technique used is sacrificial or impressed current method. Sacrificial method is normally used in smaller scale protection and impressed current method is suitable in a dynamic environment or larger scale of protection. In an impressed current method, a DC power source from a rectifier power is required to maintain the drain point voltage within a specific range so the electrons can flow from the buried anode to the cathode. However, there are many malfunctions in the cathodic protection especially in the remote areas had remained undetected until the structure that was supposed to be protected corrodes and leaks. In this research, a software algorithm is created to be able to sense the readings of drain point, shunt current, transformer rectifier voltage, temperature, humidity and to response to multiple levels of CP malfunctions using interactive graphical method and mapping system. A multiple platform of remote data communication was proposed to improve the current CP monitoring system. A brief study on Petronas underground gas pipeline system was made to help understand the current technology used in monitoring CP and to analyze the problem faced by the current CP monitoring system. As the world is emerging into mobile technology, an innovative plan was made to combine traditional monitoring system into smart phones mobile application. An electronic prototype were designed, fabricated and tested to monitor the pipelines drain point voltage, transformer rectifier voltage, shunt current, humidity and temperature using a local server system whereby all the data collected are stored on a local storage before synchronizing to the internet’s web server database using the cloud system. In the software development, a mobile application was implemented on an Android platform to enable mobile users to view and monitor the cathodic protection seamlessly from anywhere around the world. A local server running on windows platform was used to capture and display the readings on graph. The local server uses push emails and short message service (SMS) to alert to the user whenever there is a malfunction detected. The test results indicated that the proposed system is able to reduce the overall operating cost, increase service productivity in maintaining the system and reduce the need for manpower. Furthermore, the integration with a smart phone device is considered to be more user friendly, increase data portability and easy to access using various platform.